(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The first English romantic artist was Fuseli's follower William Blake (1757-1827). Unlike his happier predecessor Henry Fuseli, Blake lived a difficult life, full of trials and unfinished works. This article illustrates his originative life period.